Risk of cerebrovascular accidents according to weather and pollution features. (11th May 2021) - Biondi-Zoccai, G; Anticoli, S; Pezzella, F; Di Giosa, A; Marchegiani, G; Calcagno, S; Di Pietro, R; Versaci, F
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND: Despite mounting evidence, there is uncertainty on the impact of the interplay between weather and pollution features on the risk of acute cerebrovascular events (CVE). PURPOSE: We aimed at appraising role of weather and pollution on the daily risk of CVE. METHODS: Anonymized data from a hub CVE center in a metropolitan area were collected analyzed according to weather and pollution on the same and the preceding days. Generalized additive models were used to explore the impact of individual and combined factors on the risk of daily CVE. RESULTS: We collected data from 2012 to 2017, including a total of 2534 CVE, with a 1.56 daily rate (bootstrapped 95% confidence interval 1.48-1.64). In particular, CVE were distinguished as follows: ischemic stroke, hemorrhagic stroke, arterial dissection, ruptured aneurysm, and transient ischemic attacks, with daily rates ranging from 1.422 for stroke to 0.005 for ruptured aneurysm. Unadjusted analysis showed that daily temperature, atmospheric pressure, and humidity, among weather features, were all significantly associated with CVE (all P < 0.05). Similarly, concentrations of carbon monoxide, nitrogen dioxide, nitrogen oxides, ozone, and particulate matter <10 µm (PM10), among pollution features, were all significantly associated with CVE (all P < 0.05). Multivariable analysis, also adjusted for season, showed that CVE were significantly and inversely associated with same-day minimum temperature (P < 0.001), atmospheric pressure (P = 0.007), and humidity (P < 0.001), as well as significantly and positively associated with nitrogen dioxide (P = 0.005) and PM10 (P < 0.001). CONCLUSION: Cerebrovascular events, and stroke in particular, are more common in days with lower temperature, pressure and humidity, and higher concentrations of NO2 and PM10.